Analysis of Organelle Targeting by DIL Domains of the Arabidopsis Myosin XI Family - Sattarzadeh, Amirali; Schmelzer, Elmon; Hanson, Maureen R. (Frontiers in Plant Science, 2011)
The Arabidopsis thaliana genome encodes 13 myosin XI motor proteins. Previous insertional mutant analysis has implicated substantial redundancy of function of plant myosin XIs in transport of intracellular organelles. Considerable information is available about the interaction of cargo with the myosin XI-homologous yeast myosin V protein myo2p. We identified a region in each of twelve myosin XI sequences that correspond to the yeast myo2p secretory-vesicle binding domain (the “DIL” domain). Structural modeling of the myosin DIL domain region of plant myosin XIs revealed significant similarity to the yeast myo2p and myo4p DIL domains. Transient expression of YFP fusions with the Arabidopsis myosin XI DIL domain resulted in fluorescent labeling of a variety of organelles, including the endoplasmic reticulum, peroxisomes, Golgi and nuclear envelope. With the exception of the YFP: MYA1-DIL fusion, expression of the DIL-YFP fusions resulted in loss of motility of labeled organelles, consistent with a dominant-negative effect. Certain fusions resulted in localization to the cytoplasm or to unidentified vesicles. The same YFP-domain fusion sometimes labeled more than one organelle. Expression of a YFP fusion to a yeast myo2p DIL domain resulted in labeling of plant peroxisomes. Fusions with some of the myosin XI domains resulted in labeling of known cargoes of the particular myosin XI; however, certain myosin XI YFP fusions labeled organelles that had not previously been found to be detectably affected by mutations nor by expression of dominant negative constructs.